The potential of the mohamad toha area as a street food tourism destination in cirebon city - Khalim, Abdul; Dewi, Ratna Puspita (Journal of Gastro Tourism, 2024)
The Mohamad Toha area is located in Kebonbaru Village, Kejaksan District, Cirebon City, in the center of Cirebon city and only ± 200m from the Cirebon mayor's office. This street is filled with various food vendors presenting typical Indonesian flavors with a local touch, from heavy food to sweet snacks, this street has everything to pamper the taste buds of its visitors. This research aims to discover the potential of the Mohamad Toha area as a tourist destination in Cirebon City. By using a qualitative approach and 3A’s analysis, this research identifies what culinary tourism in the Mohamad Toha area could be a potential tourist visit, as well as how to analyze the 3A’s, namely the attractions presented, the amenity available in the area and the accessibility to the area. The findings show that the Mohamad Toha area of Cirebon City has culinary tourism potential which can be an attraction for local tourists and tourists who are on holiday in Cirebon City, and based on the 3A’s analysis the Mohamad Toha Tourism Area is quite supportive of being a culinary tourism attraction in Cirebon City, having various attractions, street culinary, easy access and close to the city center, as well as sufficient supporting facilities.